A Pilot Study Addressing the Impact of Religious Practice on Quality of Life of Breast Cancer Patients During Chemotherapy - Paiva, Carlos Eduardo (Journal of religion and health, 2013)
The aim of this preliminary study was to investigate whether religious practice can modify quality of life (QoL) in BC patients during chemotherapy. QoL and religion practice questionnaire (RPQ) scores were evaluated in a sample of BC patients in different moments. Before chemotherapy initiation, women with lower physical and social functional scores displayed higher RPQ scores. On the other hand, low RPQ patients worsened some QoL scores over time. Body image acceptance was positively correlated with religious practice and specifically praying activity. This preliminary study suggests the importance of religion in coping with cancer chemotherapy.